Possible risk factors for the development of children with congenital heart disease (Research, Society and Development, 2021)
Objective: To investigate the correlation between sociodemographic, surgical, nosological factors and neuropsychomotor and language development in children with congenital heart disease and to observe the effects of multidisciplinary intervention on the development of these children. Method: descriptive, experimental, and longitudinal study of children aged between 10 months and 9 years with congenital heart disease who were evaluated in relation to motor, cognitive and language development and followed up for a period of up to one year. The socio-demographic data and the history of neuropsychomotor development were obtained from an interview with the mother or caregivers, and the surgical and nosological data were extracted from the hospital records where they were operated and have been followed up since birth. Results: There was no correlation of any kind between length of stay and later development of the child. The correlation length of hospital stays x results of the PROC and CDC Tests was not significant, that is, the 07 children analyzed did not present discrepant results when compared to each other or to each other and the longer or shorter length of stay. There was also no correlation between development over the year and length of stay or number of surgeries. It is observed that all children have an adverse language condition. It can be said that most advanced from where they were when evaluated, after the proposed intervention, sustaining the importance of a multidisciplinary treatment. Conclusion: It was also noted the importance of multidisciplinary intervention in the development of these children and, consequently, improving their quality of life.